2016
DOI: 10.1074/mcp.m115.055897
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-level Robust Ridge Regression Improves Estimation, Sensitivity, and Specificity in Data-dependent Quantitative Label-free Shotgun Proteomics

Abstract: Peptide intensities from mass spectra are increasingly used for relative quantitation of proteins in complex samples. However, numerous issues inherent to the mass spectrometry workflow turn quantitative proteomic data analysis into a crucial challenge. We and others have shown that modeling at the peptide level outperforms classical summarization-based approaches, which typically also discard a lot of proteins at the data preprocessing step. Peptide-based linear regression models, however, still suffer from u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 49 publications
3
127
0
Order By: Relevance
“…MSqRob has been described in detail in Goeminne et al (2016) 9 . Briefly, for each protein, the log2-transformed peptide intensities for peptide = 1, … , in run = 1, … , are modeled as follows:…”
Section: Msqrobmentioning
confidence: 99%
“…MSqRob has been described in detail in Goeminne et al (2016) 9 . Briefly, for each protein, the log2-transformed peptide intensities for peptide = 1, … , in run = 1, … , are modeled as follows:…”
Section: Msqrobmentioning
confidence: 99%
“…Generally, for quantification, either stable isotopic labels are introduced in the analytes followed by isotope dilution analysis (IDA) or chromatographic signal intensities are correlated with peptide or protein abundances. The latter way called “label free” avoids chemical reactions, but has limitations in accuracy and has per se no multiplexing options …”
Section: Introductionmentioning
confidence: 99%
“…The latter way called "label free" avoids chemical reactions, but has limitations in accuracy and has per se no multiplexing options. [6][7][8][9][10] Generally, the alternative methodology relies on labeling peptides with stable isotopes introducing a well-defined and sufficient mass difference between samples and standard. The labeling can be done in many ways and stable isotopes are most commonly 15 N and 13 C or 18 O and many possible combinations of them, which allow using MS/ MS methods or very high resolution MS or combinations of both.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of outlier peptides on the final linear model fit can be mediated by various weighting strategies (e.g. see Goeminne et al (2016)). However, for modelling changes in PTM abundance, it would be useful to obtain effect sizes for peptides that specifically interact with a given treatment and separate them from effect sizes for other parameters that may be interacting with these peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Simpler models (e.g. those used by (Choi et al (2014) and (Goeminne et al (2016)) minimise the potential for overfitting found in more complex models. However, when many potential sources of variability exist it may be necessary to fit increasingly complex models wherein the choice of terms included, particularly any interaction terms, may need to be decided on a protein-by-protein basis.…”
Section: Introductionmentioning
confidence: 99%